2010
DOI: 10.1038/ncomms1146
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic prophages help bacteria cope with adverse environments

Abstract: Phages are the most abundant entity in the biosphere and outnumber bacteria by a factor of 10. Phage DNA may also constitute 20% of bacterial genomes; however, its role is ill defined. Here, we explore the impact of cryptic prophages on cell physiology by precisely deleting all nine prophage elements (166 kbp) using Escherichia coli. We find that cryptic prophages contribute significantly to resistance to sub-lethal concentrations of quinolone and β-lactam antibiotics primarily through proteins that inhibit ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
566
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(635 citation statements)
references
References 58 publications
31
566
5
1
Order By: Relevance
“…Error bars, SD. (Wang et al, 2010), however, has demonstrated that loss of the entire DLP12 prophage appears to reduce biofilm formation by BW25113; the reason for this discrepancy is not clear, but it may indicate that other DLP12 genes play an important role in this strain. With respect to the results presented here, we suggest that the contrasting results are due to the different mechanisms that these strains use to accomplish biofilm formation, since fimbriae expression is low in PHL628 and mannose had no affect on its aggregation properties (data not shown).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Error bars, SD. (Wang et al, 2010), however, has demonstrated that loss of the entire DLP12 prophage appears to reduce biofilm formation by BW25113; the reason for this discrepancy is not clear, but it may indicate that other DLP12 genes play an important role in this strain. With respect to the results presented here, we suggest that the contrasting results are due to the different mechanisms that these strains use to accomplish biofilm formation, since fimbriae expression is low in PHL628 and mannose had no affect on its aggregation properties (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…Prophage genes have been found to be upregulated in biofilm cells from several genera, yet the exact role that they play is unclear (Stanley & Lazazzera, 2004;Wang et al, 2010;Whiteley et al, 2001). Phage exposure and prophage activity have been implicated in biofilm dispersion, enhanced biofilm traits such as antibiotic resistance, attachment and phage tolerance, and in metabolite recycling (Wang et al, 2010;Webb et al, 2003Webb et al, , 2004. Work by Rice & Bayles has also shown that a phage-like holin cidA is important for lytic release of DNA, the latter being necessary for normal biofilm formation by Staphylococcus (Bayles, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that phage elements have an important role in generating diversity inside E. coli biofilms (Wang et al, 2009), and excision of e14, CP4-57, rac and CPS-53 prophages generate isogenetic strains with different phenotypes, including those of motility and growth (Wang et al, 2010). Induction of transposition in prokaryotes under cellstress conditions is potentially important in creating diversity facilitating adaptation to stressful environments (Hall, 1998;Petersen et al, 2002;Zhang and Saier, 2009a), and IS5 hopping upstream of flhD þ is an adaptive mutation.…”
Section: Discussionmentioning
confidence: 99%
“…[48] However, far from being "junk" DNA, many deactivated prophage regions are conserved [48] and experimental deletions of these cryptic prophage genes in E. coli has revealed that they positively contribute to bacterial fitness. [49] Prophage sequences are frequently successfully repurposed by bacteria. Numerous major bacterial innovations stem from the co-option of viral hardware including gene transfer agents (virus-like particles that transfer bacterial DNA only) [50] and type VI secretion systems (phage-derived syringes to inject or puncture neighboring cells).…”
Section: Temperate Phages As Sources Of Genetic Variation For Evolumentioning
confidence: 99%